Quality of prenatal: impact of infrastructure and work process (Research, Society and Development, 2020)
Objective: to assess the quality of prenatal care at usual risk using structure and process indicators. Methodology: quantitative research of the observational descriptive transversal observational type that followed the Donabedian theoretical framework. Data collection took place through the use of a questionnaire called IPR-PRENATAL in 13 Family Health Strategies, from September to October 2017. Results: it was shown that, in general, the infrastructure was considered adequate. In the variable work process, 92.3% of the monitored pregnant women had at least six prenatal consultations and that of the puerperium, 69.2% completed the first prenatal consultation in the first trimester of pregnancy, 53.8% of the professionals identify whether the first consultation was after the fourth month of pregnancy. Final considerations: it is concluded that the Family Health Strategies are structurally satisfactory with regard to the supply of permanent equipment and medication and supplements in prenatal care. As for the work process, it is necessary to invest in increasing the use of indicators in relation to information management and the use of light technologies.